Nurses Experience of Prone Position in The Absence of Positioning Tool, and Suggestion of Prone Position Tool: A Phenomenology Study - Sriyono, Sriyono; Zulkarnain, Hakim; Wahyuni, Erna Dwi; Sudarmaji, Wikan Purwihantoro; Proboningsih, Jujuk; Mosteiro-Diaz, María Pilar (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
During the COVID-19 pandemic which is a non-natural disaster, the ARDS cases (Acute Respiratory Disease Syndrome) rocketed. Despite the advantages of prone positioning for ARDS care, ICU staff seldom use it due to the unavailability of positioning tools, making it a challenging task for nurses. This study aims to investigate nurses' experiences with manual prone positioning and propose ICU-friendly prone position tools. This research method used a qualitative phenomenology theory study to 15 ICU nurses who were experienced in prone positioning at least 10 times to intubated patients and had complaints about the intervention. The experience was gathered using structured questions and recorded. The data was analyzed following Colaizzi’s thematic method, and all the emerged themes were collected and reported. The research results show that fifteen interviewed nurses noted that prone positioning is physically demanding and requires a coordinated team with a minimum of three staffs, 2 handles patient positioning, 1 leader securing the intubation tube. Before starting, the team assesses the difficulty level. Recommended tools include a slide sheet with handles, a modified Vollman prone positioner, and a crane-like prone harness. The conclusion is nurses find tools highly beneficial for prone positioning but will improvise with available resources like underpads as a ring-shaped pillow if tools are unavailable.